Vascular Anatomy in Laparoscopic Colectomy for Right Colon Cancer. Issue 8 (August 2016) - Lee, Sang Jae; Park, Sung Chan; Kim, Min Jung; Sohn, Dae Kyung; Oh, Jae Hwan
Abstract : BACKGROUND: The vascular anatomy in the right colon varies; however, related studies are rare, especially on the laparoscopic vascular anatomy of living patients. OBJECTIVE: The purpose of this study was to describe vascular variations around the gastrocolic trunk, middle colic vein, and ileocolic vessels in laparoscopic surgery for right-sided colon cancer. DESIGN: This is a retrospective descriptive study of patients undergoing laparoscopic colectomy for right colon cancer. SETTINGS: The study was conducted at a single tertiary institution in Korea. PATIENTS: Consecutive patients with right colon cancer who underwent laparoscopic right colectomy using the cranial-to-caudal approach (N = 116) between January 2014 and April 2015 were included. MAIN OUTCOME MEASURES: Three colorectal surgeons took photographs and videos of the vascular anatomy during each laparoscopic right colectomy, and these were analyzed for vascular variations. RESULTS: We classified venous variations around the gastrocolic trunk into 2 types (3 subtypes), type 1 (n = 92 (79.3%)), defined as 1 or 2 colic veins draining into the gastrocolic trunk, and type II (n = 24 (20.7%)), defined as having no gastrocolic trunk. We also investigated the tributaries of the superior mesenteric vein. One, 2, and 3 middle colic veins were found in 86 (74.1%), 26 (22.4%), and 4 patients (3.5%). The right colic vein drained directly into the superior mesenteric vein in 22 patients (19.0%). All of the patients had a single ileocolic vein draining into the superior mesenteric vein and a single ileocolic artery from the superior mesenteric artery. The right colic artery from the superior mesenteric artery was present in 38 patients (32.7%). The ileocolic artery passed the superior mesenteric vein anteriorly or posteriorly in 58 patients (50%) each. LIMITATIONS: Unlike cadaver or radiological studies, we could not clarify the complete vessel paths. CONCLUSIONS: We classified vascular anatomic variations in laparoscopic colectomy for right colon cancer, which could be helpful for colorectal surgeons.